2016
DOI: 10.1007/s00709-015-0937-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of young petiole galls on the narrow-leaf cottonwood, Populus angustifolia, by the sugarbeet root aphid, Pemphigus betae

Abstract: An insect-induced gall is a highly specialized structure resulting from atypical development of plant tissue induced by a reaction to the presence and activity of an insect. The insect induces a differentiation of tissues with features and functions of an ectopic organ, providing nutrition and protection to the galling insect from natural enemies and environmental stresses. In this anatomical and cytological study, we characterized how the gall-inducing aphid Pemphigus betae reshapes the leaf morphology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
6
0
1
Order By: Relevance
“…A histological study of Pemphigus betae Doane leaf galls induced on Populus angustifolia (James) demonstrated modified structure of vascular bundles that facilitate aphid access to the phloem, eliminating the need for stylet penetration into or around cells (Richardson et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A histological study of Pemphigus betae Doane leaf galls induced on Populus angustifolia (James) demonstrated modified structure of vascular bundles that facilitate aphid access to the phloem, eliminating the need for stylet penetration into or around cells (Richardson et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2012; Richardson et al . 2017; Kmieć et al . 2018; Kot & Kmieć 2020).…”
Section: Introductionunclassified
“…The nutritive tissue is organelle-rich, frequently including visible nucleoli, enlarged or fragmented vacuoles, dense cytoplasm, and high numbers of Golgi apparatus, endoplasmic reticulum, and ribosomes, which are traits indicative of the high metabolic status of these cells [17,18,19,20]. Secondly, this tissue comprises high concentrations of lipids, proteins, and carbohydrates, which supports its function as an enhanced source of nutrition to the developing insect [21,22]. …”
Section: The Galling Traitmentioning
confidence: 99%
“…Galls are alterations of plant tissues caused by gall-inducing stimuli contained in saliva injected during feeding by aphids, in maternal secretions injected during oviposition of sawflies, in larval secretions of unknown origin from cynipid galls wasps (ALMADA;FERNANDES 2011;RICHARDSON et al 2017). It causes cell hypertrophy and tissue hyperplasia (FERREIRA;MAGALHÃES et al 2014), responsible for the various structural gall shapes (ISAIAS et al 2013(ISAIAS et al , 2015.…”
Section: Introductionmentioning
confidence: 99%